ADSORÇÃO DE DOXORRUBICINA EM GRAFENO: UM ESTUDO DE PRIMEIROS PRINCÍPIOS - Tonel, Mariana Zancan (2013)
Graphene has attracted great interest from the scientific community since it was demonstrated its stability in 2004. Because of their structural and electronic characteristics, offers a wide variety of applications, such as in the electronics industry and medicine. Graphene is a single layer of graphite in which carbon atoms are arranged in hexagonal form. Meanwhile, doxorubicin (DOX) is a drug widely used for the treatment of various cancers. However, this molecule has a high toxicity mainly in the cardiovascular system. Recent experimental studies have demonstrated that the combination of doxorubicin and graphene can kill malignant cells selectively. This process is also associated with ambient temperatures due to the ability of carbon nanostructures such as graphene and carbon nanotube that can convert infrared radiation into vibrational energy generating heat and causing apoptosis of the malign cells. In this work, we present the structural and electronic properties of graphene, pure and vacancy-type defects, interacting with the DOX molecule by density functional theory (DFT) making use of computer code SIESTA. The results showed that DOX interacting with the pure graphene has a biding energy in the range from 0.88 to 1.09 eV (LDA and GGA, respectively) and the graphene vacancy type defect binding energy is about 1.09 to 0.84 eV (LDA and GGA, respectively). Likewise, it is observed that no major changes in the original electronic properties of graphene. Also, in this work was analyzed by ab initio molecular dynamics (MD-AI) position of the molecule DOX against the graphene temperature variation and it is noted that the largest spacing occurs at 300K for both as pure graphene for graphene with vacancy-type defect interacting with DOX.